Web Application Vulnerabilities: A Comprehensive Study of Attack Techniques and Countermeasures - Abhishek Jagtap; Anurag Yewale; Omkar Parve; Vikas Magar (Vidhyayana - An International Multidisciplinary Peer-Reviewed E-Journal - ISSN 2454-8596, 2023)
The significance of secure computer systems is becoming more and more clear as more computer systems are used to automate corporate processes and store confidential material. This significance is made more apparent by the fact that applications and computer systems are scattered and accessed via unsecure connections, including the Internet. The Internet has become a crucial component for governments, corporations, financial institutions, and millions of users in their day-to-day lives. Computer networks enable a variety of operations that, if lost, would seriously impair the operation of these companies. As a result, cybersecurity-related challenges have evolved into national security-related issues. The challenge of safeguarding the Internet is difficult. This paper presents certain recognized vulnerabilities of information security, classifies them, and evaluates safeguarding measures and methods for opposing the vulnerabilities.